Intercropping of Saccharum spp. with Dictyophora indusiata: effects on microbial communities and metabolite profiles during bagasse degradation - Duan, Mingzheng; Wu, Xiaojian; Long, Shengfeng; Huang, Hairong; Li, Xiang; Li, Yijie; Li, Changning; Feng, Bin; Chen, Jiafu; Zhong, Defa; Chen, Zhendong; Wang, Zeping (Frontiers in Microbiology, 2025)
BackgroundIntercropping Saccharum spp. (sugarcane) with the fungus Dictyophora indusiata together with bagasse amendment represents an innovative circular agriculture method that can enhance soil health, boost sugarcane yields, and increase farm profitability. Understanding the process by which D. indusiata degrades bagasse is key to optimizing this method.AimsThis study aims to clarify the microbial and metabolic processes involved in bagasse degradation by D. indusiata in the sugarcane intercropping system.MethodsChemical composition analysis, metabarcoding sequencing, and metabolomic profiling were conducted on D. indusiata-degraded bagasse (DIBA) and naturally degraded bagasse (BA).ResultsAnalysis of chemical composition revealed that only acid detergent fiber (ADF) and crude protein content differed significantly between the DIBA and BA treatments. Metabarcoding sequencing showed that DIBA significantly altered the bacterial and fungal communities, reducing microbial diversity. Metabolomic analysis indicated an enhancement of biological metabolism, particularly carbohydrate breakdown, in the DIBA treatment. Key metabolites, such as glucose, cellobiose, and D-mannose, were more abundant in DIBA samples. In addition, unique metabolites such as L-alanine, serine, and oxaloacetate were detected in the DIBA treatment, suggesting more efficient bagasse degradation compared with natural processes.ConclusionThe use of macrofungi such as D. indusiata can play a pivotal role in circular agriculture by transforming agricultural waste into valuable soil amendments. Future research should focus on the long-term impact of this system on soil quality and crop yield, as well as the underlying mechanisms, to further optimize intercropping systems and the use of fungi in agricultural waste management.